Development of Kinematic Analysis Methods for Spatial Multi-link Road Vehicle Suspensions - George, Ron; Sidhant, Ray (My University, 2018)
The fast moving, globalized vehicle industry has put extreme pressures to be able to develop new vehicles at a quicker rate while still being able to keep a high quality of the product. This has made the need for complete understanding of vehicle systems more important while having easy to use tools to make decisions crucial to be able to perform efficiently in this market. The focus of this thesis is to find and compare various methods of analyzing complex spatial multi-link suspensions and to get a better understanding of these. It also looks into the various parameters of suspension design that affect vehicle dynamic behaviour. These parameters are studied and methods to analyze them for spatial suspension are discussed. The differences between planar suspensions and spatial suspensions in analysis methods are also reviewed. Instantaneous Screw axis is an important concept that is explained and used to understand the behaviour of the spatial suspension and its complex three dimensional motion. The instantaneous screw axis for the chassis is also considered in a specific case. Basic graphical methods based on Kennedy's theorem are applied for simple planar suspension analysis and to find the roll center. It is found that these simple methods cannot be used for spatial suspensions which do not have a motion in one plane. Thus, Y= Z method, Virtual Position Method and Screw Axis Offset Method are found to be accurate methods to find the roll centers for these types of suspensions. They all give the value for the roll center which is defined as Moment Center (MC) of the chassis in this thesis and a force passing through it does not rotate the chassis. These methods define the spatial motion of the suspensions in a plane (wheel planes) for analysis. The Screw Axis Offset Method gives a clear understanding and reasoning for the differences of the roll center in spatial suspensions compared to one that can be erroneously found through approaches similar to those used in planar methods. These are also verified using various multibody models and a model of a production vehicle suspensions. Finally the instantaneous screw axis for a chassis is also looked into in brief. The instantaneous screw axis of the chassis with and without steering input is studied and a difference in instantaneous screw axis between the two is found.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport